The Role of Oxidative Inactivation of Phosphatase PTEN and TCPTP in Fatty Liver Disease - Thang Nguyen Huu; Jiyoung Park; Ying Zhang; Hien Duong Thanh; Iha Park; Jin Myung Choi; Hyun Joong Yoon; Sang Chul Park; Hyun Ae Woo; Seung-Rock Lee (MDPI AG, 2023)
Alcoholic liver disease (ALD) and nonalcoholic fatty liver disease (NAFLD) are becoming increasingly prevalent worldwide. Despite the different etiologies, their spectra and histological feature are similar, from simple steatosis to more advanced stages such as steatohepatitis, fibrosis, cirrhosis, and hepatocellular carcinoma. Studies including peroxiredoxin knockout models revealed that oxidative stress is crucial in these diseases, which present as consequences of redox imbalance. Protein tyrosine phosphatases (PTPs) are a superfamily of enzymes that are major targets of reactive oxygen species (ROS) because of an oxidation-susceptible nucleophilic cysteine in their active site. Herein, we review the oxidative inactivation of two tumor suppressor PTPs, phosphatase and tensin homolog deleted on chromosome 10 (PTEN) and T-cell protein tyrosine phosphatase (TCPTP), and their contribution to the pathogenicity of ALD and NAFLD, respectively. This review might provide a better understanding of the pathogenic mechanisms of these diseases and help develop new therapeutic strategies to treat fatty liver disease.